2014
DOI: 10.1111/birt.12138
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Maternal Attitudes to Breastfeeding in Public and the Association with Breastfeeding Duration in Four European Countries: Results of a Cohort Study

Abstract: Perceived social norms may exert a stronger influence on breastfeeding outcomes than a woman's breastfeeding attitudes and knowledge. Differences between European countries in the duration of breastfeeding may be explained in part by differences in societal attitudes to breastfeeding in public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 20 publications
6
54
0
3
Order By: Relevance
“…This may be partly due to the fact that mothers with higher education levels or with jobs discontinue their breastfeeding due to certain social barriers, such as having to return to work [25], in spite of their good attitudes or interests towards breastfeeding. This result supports findings that perceived social norms may exert a stronger influence on breastfeeding outcomes than a woman's breastfeeding attitudes and knowledge [10]. The strengths of our study include having a large sample size.…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 86%
See 1 more Smart Citation
“…This may be partly due to the fact that mothers with higher education levels or with jobs discontinue their breastfeeding due to certain social barriers, such as having to return to work [25], in spite of their good attitudes or interests towards breastfeeding. This result supports findings that perceived social norms may exert a stronger influence on breastfeeding outcomes than a woman's breastfeeding attitudes and knowledge [10]. The strengths of our study include having a large sample size.…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 86%
“…Another study showed independent association between maternal perception of the acceptability of breastfeeding in public and breastfeeding practices [10]. A few studies have suggested that maternal attitude is a better predictor of infant feeding method than socio-demographic factors [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…4,5 The most recent WHO position paper stating that promotion of breastmilk substitutes and complementary foods undermines breastfeeding (including "growing-up milks" advertised for older children) is likewise consistent with the view that breastfeeding attitudes play a significant role in the decision to breastfeed and the duration of breastfeeding. 6 In line with this, attitudes toward breastfeeding in public have been given an increased importance as a research subject.…”
Section: Introductionmentioning
confidence: 76%
“…Although breastfeeding generally aligns with moral standards of mothering, breastfeeding a toddler, wet nursing or cofeeding, and breastfeeding in public (particularly uncovered) are often considered deviant (Faircloth, 2010(Faircloth, , 2013Lane, 2014;Murphy, 1999;J. A. Scott et al, 2015;Shaw, 2004;Stearns, 1999) and may fall outside legal protection in some U.S. states (Carter & McCutcheon, 2013).…”
Section: Breastfeeding In Publicmentioning
confidence: 99%